Thefleeky.co / Muhammad Hariz Hazman Hasbullah - Hasbullah, Muhammad Hariz Hazman (2021)
Thefleeky.co is an upscale online gift box business that offers a unique selection of gifts in an artistic and unique environment. Thefleeky.co will provide a custom basket option, allowing customers to choose their own present. Thefleeky.co focuses on creating distinct occasion-based gift boxes from a large selection of high-quality items. Thefleeky.co will sell to both individuals and businesses. Individuals will first produce the majority of its revenue through word-of-mouth referrals, but as time goes on, businesses will become a larger share of sales. Customers can be categorised based on whether they're presenting the giftbox to business associates, friends, family, or networking contacts. The store has a large selection of hard-to-find and unique gift options for people of all ages. Customers can explore basic gift boxes by "event" category in a range of price points through Thefleeky.co's social media platforms, which include Facebook and WhatsApp. Customers can choose, buy, and pay for their gift box on Facebook or by phoning the number clearly advertised on the website. Thefleeky.co distinguishes itself by focusing on distinctive giftboxes, selling them inexpensively, and delivering services with a uniquely personal touch for both buyers and receivers, encouraging repeat business and recommendations. Gift wrapping is also offered in a variety of styles. We provide gorgeous and elegant present packaging alternatives to fit any taste and budget, from budget-friendly gift wrapping to high-end gift boxes.